2018
DOI: 10.1371/journal.pbio.2003862
|View full text |Cite
|
Sign up to set email alerts
|

Compositional shifts in root-associated bacterial and archaeal microbiota track the plant life cycle in field-grown rice

Abstract: Bacterial communities associated with roots impact the health and nutrition of the host plant. The dynamics of these microbial assemblies over the plant life cycle are, however, not well understood. Here, we use dense temporal sampling of 1,510 samples from root spatial compartments to characterize the bacterial and archaeal components of the root-associated microbiota of field grown rice (Oryza sativa) over the course of 3 consecutive growing seasons, as well as 2 sites in diverse geographic regions. The root… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
287
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(328 citation statements)
references
References 65 publications
40
287
1
Order By: Relevance
“…It could be that integrating these factors in future EcoFAB studies might increase the variability of the system. It will be important to investigate the reproducibility as well as the morphological and metabolic responses of plants to microbial communities and soil mineralogy, as natural soils were identified as main contributors shaping root morphology, plant C exudation, plant–microbe interactions, and rhizosphere extension (Bulgarelli et al ., ; Holz et al ., ; Koebernick et al ., ; Edwards et al ., ). Overall, we conclude that the reproducibility of plant traits in soil extract EcoFABs is a promising first step towards developing plant growth systems generating reproducible data that are relevant to field environments.…”
Section: Discussionmentioning
confidence: 97%
“…It could be that integrating these factors in future EcoFAB studies might increase the variability of the system. It will be important to investigate the reproducibility as well as the morphological and metabolic responses of plants to microbial communities and soil mineralogy, as natural soils were identified as main contributors shaping root morphology, plant C exudation, plant–microbe interactions, and rhizosphere extension (Bulgarelli et al ., ; Holz et al ., ; Koebernick et al ., ; Edwards et al ., ). Overall, we conclude that the reproducibility of plant traits in soil extract EcoFABs is a promising first step towards developing plant growth systems generating reproducible data that are relevant to field environments.…”
Section: Discussionmentioning
confidence: 97%
“…Microbial communities undergo shifts in diversity and composition as seasons change and their hosts mature (3,4). However, temporal variation of microbe-microbe interactions within these communities has not been characterized.…”
Section: Mainmentioning
confidence: 99%
“…There have been a limited number of reports in the literature on the temporal dynamics of microbial communities (Shi et al, 2015;Fierer, 2017;Edwards et al, 2018;Xu et al, 2018). Agroecosystems provide an excellent platform for analyzing temporal changes in microbial communities because the experimental design allows for replicated plots, which are large enough to be sampled multiple times.…”
Section: Dynamics Of Microbial Communitiesmentioning
confidence: 99%
“…This highlights the dynamic nature of the microbial communities that are associated with plant roots and suggests that single time point sampling only provides a limited snapshot of complex soil microbial communities. While some have suggested that the changes observed in microbiomes over time are related to plant development (Chaparro et al, 2014), more recent work show that in some cases residence time in the soil rather than plant development was more important (Dombrowski et al, 2017) or that both development and residence time play roles (Edwards et al, 2018) in temporal changes. This study clearly showed that changes in the root, rhizosphere and soil microbiome occur throughout the growing season in temperate soils where maize is grown.…”
Section: Dynamics Of Microbial Communitiesmentioning
confidence: 99%